2011
DOI: 10.1021/jf104267c
|View full text |Cite
|
Sign up to set email alerts
|

Norsesquiterpene Glycosides in Bracken Ferns (Pteridium esculentum and Pteridium aquilinum subsp.wightianum) from Eastern Australia: Reassessed Poisoning Risk to Animals

Abstract: Austral bracken Pteridium esculentum contains three unstable norsesquiterpene glycosides: ptaquiloside, ptesculentoside, and caudatoside, in variable proportions. The concentration of each of the glycosides was determined in this study as their respective degradation products, pterosin B, pterosin G and pterosin A, by HPLC-UV analysis. Samples of P. esculentum collected from six sites in eastern Australia contained up to 17 mg of total glycoside/g DW, with both ptaquiloside and ptesculentoside present as major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 22 publications
3
47
0
Order By: Relevance
“…Bearing these limitations in mind, the number of VOCs found in our six study species (22-33) was comparable to those recorded in other fern species analysed to date (Briggs & Sutherland 1947;Juliani et al 2004;Cheng & Mao 2005;Naseri et al 2006;Miyazawa et al 2007;Radulovi c et al 2008;Imbiscuso et al 2009;Fons et al 2010;Fletcher et al 2011). More direct comparisons are hampered by methodological differences in the extraction and analytical procedures in the different studies.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Bearing these limitations in mind, the number of VOCs found in our six study species (22-33) was comparable to those recorded in other fern species analysed to date (Briggs & Sutherland 1947;Juliani et al 2004;Cheng & Mao 2005;Naseri et al 2006;Miyazawa et al 2007;Radulovi c et al 2008;Imbiscuso et al 2009;Fons et al 2010;Fletcher et al 2011). More direct comparisons are hampered by methodological differences in the extraction and analytical procedures in the different studies.…”
Section: Discussionsupporting
confidence: 78%
“…Chemically, these compounds belonged to fatty acid derivatives (FADs; 16 substances), aromatics (eight), Table 1. VOCs recorded in the six study species, with numbers representing percentage of amounts relative to all recorded VOCs, as well as indication of previous records of these substances among ferns (based on Briggs & Sutherland 1947;Juliani et al 2004;Cheng & Mao 2005;Naseri et al 2006;Miyazawa et al 2007;Radulovi c et al 2008;Imbiscuso et al 2009;Fons et al 2010;Fletcher et al 2011) and angiosperms (based mainly on Knudsen et al 2006). monoterpenes (ten), sesquiterpenes (one), sulphur-containing compounds (one), irregular terpenes (one) and heterocyclic aldehydes (one).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Further detailed investigation concluded that the risk to health of persons consuming meat from livestock exposed to pyrrolizidine-containing plants in northern Australia was negligible (Fletcher et al 2011a). The risks from indospicine in meat and ptaquilosides in milk are not considered high, but are still under investigation (Fletcher et al 2011b). However, most exposure to the source plants is from grazing situations rather than from contaminated feedstuffs.…”
Section: Other Plant Toxinsmentioning
confidence: 99%
“…In laboratory rodents, PtQ induces solid tumors in the ileum, the lung, mammary glands and the urinary bladder, in addition to severe or deadly acute intoxications in wild deer and cattle when ingesting bracken fern, an invasive plant worldwide . The transfer of PtQ and other similar illudanes from animal feed to meat and milk of exposed animals raises concerns about its impact on human health related to gastric malignancies . Brackens synthesise other closely related illudanes ( 1 b ‐ 1 g, Figure ) endowed with similar biological damaging potential.…”
Section: Introductionmentioning
confidence: 99%